Cardiac resynchronisation therapy is not associated with a reduction in mortality or heart failure hospitalisation in patients with non-left bundle branch block QRS morphology: meta-analysis of randomised controlled trials. Issue 18 (12th February 2015) - Cunnington, Colin; Kwok, Chun Shing; Satchithananda, Duwarakan K; Patwala, Ashish; Khan, Muhammad A; Zaidi, Amir; Ahmed, Fozia Z; Mamas, Mamas A
Abstract : Objectives: Recently published clinical guidelines recommend cardiac resynchronisation therapy (CRT) for patients with heart failure (HF) with reduced LVEF and non-left bundle branch block (non-LBBB) QRS morphology. We sought to define the potential benefit of CRT in these patients through meta-analysis of randomised controlled trials (RCTs) that have reported outcomes in patients with non-LBBB QRS morphology. Methods: We searched MEDLINE and EMBASE for RCTs of CRT that reported outcomes according to QRS morphology. We performed meta-analysis of these RCTs to assess the effect of CRT on the end points of death, HF hospitalisation, and the composite of death and HF hospitalisation. Results: Five RCTs were analysed, including 6523 participants (1766 with non-LBBB QRS morphology). CRT was not associated with a reduction in death and/or HF hospitalisation in subjects with non-LBBB QRS morphology (HR 0.99 95% CI 0.82 to 1.20). Conclusions: CRT is not associated with a reduction in death or HF hospitalisation in patients with non-LBBB QRS morphology. Wide QRS with non-LBBB morphology remains an area of uncertainty for CRT, which is included in the recent European Society of Cardiology guidelines with a weaker strength of recommendation, but is not supported by a dedicated RCT.